1988
DOI: 10.1111/j.1399-3054.1988.tb01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Proline accumulation and nitrate reductase activity in contrasting sorghum lines during mid‐season drought stress

Abstract: Peacock, J. M. 1988. Proline accumulation and nitrate reductase activity in contrasting sorghum lines during mid-season drought stress. -Physiol. Plant. 74: 418-426.Six lines of sorghum {Sorghum bicolor L. Moench) with differing drought resistance (IS 22380, ICSV 213, IS 13441 and SPH 263, resistant and IS 12739 and IS 12744, susceptible) were grown under field conditions in the semi-arid tropics and analysed for proline and nitrate reductase activity (NRA; EC 1.6 6.1) during a mid-season drought. The resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 23 publications
1
23
0
3
Order By: Relevance
“…The results showed that Beni Mestina variety is highly resistant with a production rate of 133. Many studies report that proline accumulated in plants under unfavorable conditions (Sivaramakrishnan et al, 1988) which reflects the character of resistance to water stress (Greenway …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that Beni Mestina variety is highly resistant with a production rate of 133. Many studies report that proline accumulated in plants under unfavorable conditions (Sivaramakrishnan et al, 1988) which reflects the character of resistance to water stress (Greenway …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been reported that the accumulation of proline in transgenic plants (Surender Reddy et al, 2015) can mitigate significantly the damage caused by salinity. Moreover, in wildtype plants, it has been observed that genotypes with a higher tolerance to drought stress accumulate a higher concentration of proline on tolerant plants compared to susceptible plants (Sivaramakrishnan et al, 1988). In contrast, reactive oxygen species accumulation was consistently higher in plants of the variety TX430 compared to the variety R19 reaching a more considerable difference in the phenological phase of five leaves.…”
Section: Discussionmentioning
confidence: 87%
“…'accumulation de composes organiques azotes comme Ia proline (1-Iubac et al, 1969;Stewart, 1979;Briens et Larher, 1982 ;Rodriguez et Heyser, 1988 ;Goldhirs et al, 1990). Cet acide amine est retenu par de nomhreux auteurs comme indicateur de Ia tolerance au froid, a Ia secheresse ou a Ia salinite (Flowers et Yeo, 1977;Calmes et al, 1985 ;Paquin et Pelletier, 1980) (Hubac et Guerrier, 1972 ;Hanson et al, 1979;Sivaramakrishnan et al, 1988) considerent que ! 'accumulation de Ia proline se produit lorsque Ia plante est en conditions defavorables.…”
Section: Introductionunclassified